Achieved serum magnesium concentrations and occurrence of delayed cerebral ischaemia and poor outcome in aneurysmal subarachnoid haemorrhage. Issue 7 (29th November 2006) - Dorhout Mees, Sanne M; van den Bergh, Walter M; Algra, Ale; Rinkel, Gabriel J E
Abstract : Background: Magnesium therapy probably reduces the frequency of delayed cerebral ischaemia (DCI) in subarachnoid haemorrhage (SAH) but uncertainty remains about the optimal serum magnesium concentration. We assessed the relationship between serum magnesium concentrations achieved with magnesium sulphate therapy 64 mmol/day and the occurrence of DCI and poor outcome in patients with SAH. Methods: Differences in magnesium concentrations between patients with and without DCI and with and without poor outcome were calculated. Quartiles of last serum magnesium concentrations before the onset of DCI, or before the median day of DCI in patients without DCI, were related to the occurrence of DCI and poor outcome at 3 months using logistic regression. Results: Compared with the lowest quartile of serum magnesium concentration (1.10–1.28 mmol/l), the risk of DCI was decreased in each of the higher three quartiles (adjusted odds ratio (OR) in each quartile 0.2; lower 95% CI 0.0 to 0.1; upper limit 0.8 to 0.9). The OR for poor outcome was 1.8 (95% CI 0.5 to 6.9) in the second quartile, 1.0 (95% CI 0.2 to 4.5) in the third quartile and 4.9 (95% CI 1.2 to 19.7) in the highest quartile. Discussion: Magnesium sulphate 64 mmol/day results in a stable risk reduction of DCI over a broad range of achieved serum magnesium concentrations, and strict titration of the dosage therefore does not seem necessary. However, concentrations ⩽1.28 mmol/l could decrease the effect on DCI while concentrations ⩾1.62 might have a negative effect on clinical outcome.